2019
DOI: 10.3390/polym11081303
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Behavior and Endothelialization of a Silk-Based Small-Caliber Scaffold In Vivo Transplantation

Abstract: A silk-based small-caliber tubular scaffold (SFTS), which is fabricated using a regenerated silk fibroin porous scaffold embedding a silk fabric core layer, has been proved to possess good cell compatibility and mechanical properties in vitro. In this study, the endothelialization ability and the steady-state blood flow of SFTSs were evaluated in vivo by implanting and replacing a common carotid artery in a rabbit. The results of the color doppler ultrasound and angiographies showed that the blood flow was cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…A study employed a 3 mm diameter tubular scaffold, produced by braiding SF yarns and coating with a SF-PGDE aqueous solution, to evaluate endothelialization and steady-state blood flow in vivo by implanting and replacing a common carotid artery in rabbits (30). Doppler ultrasound and angiography demonstrated graft patency without aneurysmal dilations or significant stenoses at any time point, with waveforms comparable to the native contralateral artery.…”
Section: Sf In Leporine Modelsmentioning
confidence: 99%
“…A study employed a 3 mm diameter tubular scaffold, produced by braiding SF yarns and coating with a SF-PGDE aqueous solution, to evaluate endothelialization and steady-state blood flow in vivo by implanting and replacing a common carotid artery in rabbits (30). Doppler ultrasound and angiography demonstrated graft patency without aneurysmal dilations or significant stenoses at any time point, with waveforms comparable to the native contralateral artery.…”
Section: Sf In Leporine Modelsmentioning
confidence: 99%
“…After implanting the grafts (1.5 mm in diameter, 1 cm long) for up to 3 months in rat models, they showed that the ideal concentration was 1.5% of silk, regarding stenosis, tissue infiltration, and intimal hyperplasia. More recently, Li et al 84 designed tubular braided scaffolds coated with silk fibroin then freeze-dried and cross-linked with PGDE. They implanted the grafts (15 mm long and 3 mm inner diameter) for 1 year in rabbits and observed that an endothelial layer had formed after 1 month and that by 3 months endothelialization was complete.…”
Section: Vascular-shaped Scaffoldsmentioning
confidence: 99%
“…Previous research has demonstrated that in vivo , only very mild inflammatory responses to SF occur ( Wang Y et al, 2008 ). Regenerated silk fibroin (RSF) has been widely utilized as an excellent biomaterial for various biomedical applications, such as cartilage regeneration ( Wang et al, 2006 ; Hong et al, 2020 ), artificial blood vessels ( Lovett et al, 2007 ; Zhang et al, 2008 ; Li et al, 2019 ), drug delivery scaffolds ( Wang X et al, 2008 ; Maity et al, 2020 ), ligament reconstruction ( Bi et al, 2021 ; Yan et al, 2021 ), bone tissue engineering ( Hofmann et al, 2007 ; Gambari et al, 2019 ), and skin tissue engineering ( Bhardwaj et al, 2015 ). RSF can be fabricated into various forms of materials, including fibers, films, porous sponges, hydrogels, scaffolds, and nanomicrospheres ( Kundu et al, 2013 ; Lu et al, 2015 ; Yan et al, 2015 ; Kapoor and Kundu, 2016 ; Choi et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%